(untitled) (SCIENCE TIME JOURNAL, 2026)
Formative assessment has become one of the most effective strategies for supporting student achievement and fostering a culture of continuous learning. Unlike summative tests, which measure learning at the end of an instructional cycle, formative assessment provides ongoing feedback to both learners and teachers, guiding the teaching process and improving outcomes. This paper explores the role of formative assessment as a driver of lifelong learning, its theoretical basis, practical strategies, and its implications for teacher professional practice. The study highlights how formative assessment promotes self-regulation, motivation, and reflection, positioning it as an indispensable element of modern pedagogy.